Medial Wall Fracture and Orbital Emphysema Mimicking Inferior Rectus Entrapment in a Child. Issue 4 (December 2015) - Collin, John; Afshar, Farid; Thomas, Steven
Orbital emphysema is commonly associated with fractures of the orbital floor or medial wall. The air often dissipates spontaneously, but rarely can cause increased intraocular pressure and even loss of vision. Entrapment of the extraocular muscles can also occur with orbital fractures and may require prompt treatment in the pediatric patient due to the risk muscle ischemia. Both conditions can cause diplopia due to restriction of eye movement and differentiation of the two etiologies is important to prevent unnecessary surgical exploration. Identification and prompt management of raised intraocular pressure is essential in patients with orbital trauma. We present a case of orbital emphysema mimicking inferior rectus entrapment following trauma in an 11-year-old boy.